USM VC HOLDS TALKS ON FUTURE COLLABORATIONS IN SURABAYA - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
SURABAYA, INDONESIA, 4 August 2016 – The Universiti Sains Malaysia (USM) ViceChancellor Professor Dato' Dr. Omar Osman had a meeting this evening with the Rector, Universitas Surabaya, Professor Dr. Joniarto Parung, Office of Institutional Collaboration Professor Dr.ec. Sujoko Efferin and the Director, Board of Scrutiny and Public Services, Professor Drs. A.J. Tjahjoanggoro to discuss on academic collaborations and student mobility to undergo studies at USM in the future.